Thermosensitive heparin‐poloxamer hydrogels enhance the effects of GDNF on neuronal circuit remodeling and neuroprotection after spinal cord injury. Issue 10 (14th July 2017) - Zhao, Ying‐Zheng; Jiang, Xi; Lin, Qian; Xu, He‐Lin; Huang, Ya‐Dong; Lu, Cui‐Tao; Cai, Jun
Abstract: Traumatic spinal cord injury (SCI) results in paraplegia or quadriplegia, and currently, therapeutic interventions for axonal regeneration after SCI are not clinically available. Animal studies have revealed that glial cell‐derived neurotrophic factor (GDNF) plays multiple beneficial roles in neuroprotection, glial scarring remodeling, axon regeneration and remyelination in SCI. However, the poor physicochemical stability of GDNF, as well as its limited ability to cross the blood–spinal cord barrier, hampers the development of GDNF as an effective therapeutic intervention in clinical practice. In this study, a novel temperature‐sensitive heparin–poloxamer (HP) hydrogel with high GDNF‐binding affinity was developed. HP hydrogels showed a supporting scaffold for GDNF when it was injected into the lesion epicenter after SCI. GDNF‐HP by orthotopic injection on lesioned spinal cord promoted the beneficial effects of GDNF on neural stem cell proliferation, reactive astrogliosis inhibition, axonal regeneration or plasticity, neuroprotection against cell apoptosis, and body functional recovery. Most interestingly, GDNF demonstrated a bidirectional regulation of autophagy, which inhibited cell apoptosis at different stages of SCI. Furthermore, the HP hydrogel promoted the inhibition of autophagy‐induced apoptosis by GDNF in SCI. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2816–2829, 2017.